Reformulating a Market-Driven Service Strategy of Community-Based Tourist Destinations Post-Pandemic Covid-19: Evidence from Indonesia - Ginta Ginting; Ike Janita Dewi (Yayasan Ilomata, 2022)
The COVID-19 pandemic has exposed tourism villages to various challenges. Tourism villages as a form of rural tourism which are managed by local people face more serious problems due to their lack of expertise. This study aims to apply customer-driven strategies in formulating strategies to market tourism villages. Employing marketing concepts of service quality, satisfaction, and revisit intention, this research investigates the mediating role of satisfaction in the relationship between service quality and revisit intention. Tourist perceptions are further analyzed based on their demographic and psychographic characteristics to provide insights into the formulation of segmentation strategies. This research collects data from 203 people who have visited tourism villages. Data were collected offline and online using Google Forms. Results of Regression Analysis with Mediation and Bonferonni's Multiple Comparison indicated that Reliability, Empathy, and Tangibles have a positive effect on satisfaction. Further, satisfaction fully mediates the effect of Reliability and Empathy on revisit intention. Meanwhile, satisfaction partially mediates the effect of Responsiveness and Tangibles on revisit intention.